Efektivitas Pelaksanaan Rehabilitasi Terhadap Pengguna Narkotika Dalam Pasal 127 Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika (Studi Kasus di Badan Narkotika Nasional Kabupaten Tuban) - Spristisia, Arum; Handayani, Tri Astuti; Yasin, Bukhari (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
This study examines the implementation of rehabilitation for narcotics users under Article 127 of Law Number 35 of 2009 and evaluates its effectiveness at the National Narcotics Agency of Tuban Regency (BNNK Tuban). This empirical legal research was conducted through interviews with the Head of the Rehabilitation Team, field observations, and literature review. The findings show that rehabilitation programs at BNNK Tuban comply with the law and BNN technical guidelines, covering integrated assessment, determination of outpatient or inpatient services, medical and psychosocial therapies, and post-rehabilitation services. The program is considered effective in improving clients’ physical, psychological, and social conditions, particularly for those consistently participating in after-care programs. However, its effectiveness is hindered by limited facilities, lack of professional staff, and persistent social stigma. This study recommends strengthening assessment mechanisms, enhancing after-care services, and promoting public education to reduce relapse rates.